2022
DOI: 10.3390/agronomy12010108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Up-Converting Luminescent Nanoparticles with Increased Quantum Yield Incorporated into the Fluoropolymer Matrix on Solanum lycopersicum Growth

Abstract: The influence of light conversion induced by glasses coated with up-converting luminescent nanoparticles on Solanum lycopersicum cultivation was studied. Nanoparticles of Sr0.46Ba0.50Yb0.02Er0.02F2.04 solid solution were used as the up-converting luminophore. These nanoparticles were able to transform IR radiation into visible light (λem = 660 nm with minor peaks at 545 nm and 525 nm). By applying the “variable” chlorophyll fluorescence (ΔF), it was shown that the cultivation of tomatoes under the photoconvers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 76 publications
1
6
0
1
Order By: Relevance
“…Excitation of Sr0.76Ba0.20Yb0.02Er0.02F2.04 nanoparticles by IR radiation at a wavelength of 975 nm induced photoluminescence with characteristic Er 3+ /Yb 3+ emission bands in the red (about 660 nm) and green (545 nm and 525 nm) regions of the spectrum (data not shown), which corresponds to the luminescence spectra of SrF2 single crystals doped with Er 3+ and Yb 3+ [17,[21][22][23][24].…”
Section: Resultsmentioning
confidence: 90%
“…Excitation of Sr0.76Ba0.20Yb0.02Er0.02F2.04 nanoparticles by IR radiation at a wavelength of 975 nm induced photoluminescence with characteristic Er 3+ /Yb 3+ emission bands in the red (about 660 nm) and green (545 nm and 525 nm) regions of the spectrum (data not shown), which corresponds to the luminescence spectra of SrF2 single crystals doped with Er 3+ and Yb 3+ [17,[21][22][23][24].…”
Section: Resultsmentioning
confidence: 90%
“…While a small upconversion to UV photons might helpful in color/flavor/nutrient boosting, NIR‐to‐visible photon upconversion offers the possibility to combine thermal management and photosynthetic photon flux enhancement. Some pilot studies of the effect of upconverting systems combined with photosynthetic systems are promising—a 12% increase in photosynthetic rate has been observed in Arabidopsis thaliana under a film containing both downconverting luminophores as well as NIR → PAR upconverting luminophores under natural light supplemented with UV; [ 122 ] NIR → PAR upconverting films have been reported to increase the leaf number (12.5%), leaf area (33%), and chlorophyll content in tomato plants under artificial lighting [ 123 ] —these studies provide a starting point for materials whose properties and efficiency could be optimized further, and tested for a variety of crops under natural solar illumination. Efforts to improve the upconversion performance of materials under lower light intensities equivalent to the incident solar radiation intensity on earth, currently involve experimenting with material parameters, nanostructuring, use of photonic structures such as dielectric microlenses to concentrate the incident light, and using plasmonic structures to get local field enhancements.…”
Section: Solar Spectrum Manipulation Technologiesmentioning
confidence: 99%
“…The other important photoconversion process involves the conversion from the non-PAR to PAR, which leads to an increase in the photosynthetic photon flux density (PPFD) and thus potentially augments photosynthesis. Some representative examples include the downconversion of UV radiation to blue [ 75 ] or red [ 76 , 77 ] radiation, and the upconversion of far-red radiation to red [ 78 ] or blue radiation [ 79 ]. UV radiation usually produces photochemical damage to the cell, reduces photosynthesis, and lowers biomass accumulation of plants [ 80 ].…”
Section: Spectral Conversion Materials In Agriculturementioning
confidence: 99%
“…Initial plant trial results have shown neutral to positive effects on microalgae growth underneath the bottom-mounted LSCs panels in the greenhouse [ 119 ]. A follow-up study concluded that these greenhouse LSCs panels had no negative impacts on tomato and cucumber production and that some varieties of crops have slightly higher values of fruit number and mass [ 79 ]. Similar LSCs panels that offer wavelength-selective power production have since entered the marketplace, and there appears to be a growing market for the wavelength selective photovoltaic panels that can generate electricity and growth crops simultaneously [ 120 ].…”
Section: Spectral Conversion Materials In Agriculturementioning
confidence: 99%